Bioinspired design for the assembly of Glypromate® neuropeptide conjugates with active pharmaceutical ingredients. (26th November 2020) - Silva-Reis, Sara C.; V. D. dos Santos, A. Catarina; García-Mera, Xerardo; Rodríguez-Borges, José E.; Sampaio-Dias, Ivo E.
Abstract : A robust and bioinspired methodology for the efficient conjugation of Glypromate® with active pharmaceutical ingredients for neurodegenerative diseases. Abstract : Neurodegenerative diseases, such as Alzheimer's and Parkinson's diseases, are a class of heterogeneous pathologies of the central nervous system (CNS) affecting millions of people worldwide. CNS-related pathologies represent a global health burden in developed and developing countries with no curative treatments currently available. Thus, the development of novel multitarget neuroprotective drugs is a health priority. In this work, a bioinspired methodology in solution-phase for the assembly and regioselective conjugation of Glypromate® neuropeptide with active pharmaceutical ingredients (APIs) is described. The main purpose is to design new hybrid molecules which may offer increased systemic resistance of Glypromate® towards proteases and/or allow the controlled release of both APIs and the neuroprotective peptide within CNS. For the synthesis of such peptide-hybrid compounds ( R )-1-aminoindane, amantadine, and memantine were selected as APIs for conjugation with Glypromate®. Furthermore, capping strategies are explored to prepare Glypromate® conjugates with more favorable pharmacodynamic profiles by masking polar exposed groups. Overall, this synthetic approach led to the development of a small library of 12 conjugates with improved drug-like properties in comparison with Glypromate®, paving the way for the discovery of novel CNS multitarget drugs. Additionally, by exploring the bis-functionalization of glutamate, the formation of chiral glutarimides is disclosed for the first time employing TBTU as the coupling reagent. This unusual reactivity of TBTU with glutamate offers a new synthetic approach for the preparation of chiral glutarimide alkaloids.